2016
DOI: 10.4317/medoral.21433
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of bisphosphonate-related osteonecrosis of the Jawsamong Mexican dentists

Abstract: BackgroundBisphosphonate-related osteonecrosis is an infrequent but potentially serious complication. Its treatment remains complex, and in some cases can be mutilating. Prevention, a correct diagnosis and opportune management are crucial.Material and MethodsA cross-sectional study was made, interviewing 410 dentists with the aim of assessing their knowledge of the subject.ResultsPractically all of the dental professionals (99.7%) were found to lack sufficient knowledge of the prevention, diagnosis and managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 8 publications
4
15
2
Order By: Relevance
“…Our findings are in line with most of previous similar studies in different countries, which reported very poor knowledge on MRONJ and BPs among dentists. 2,[13][14][15][16] This can be attributed to the insufficient exposure of dentists to these topics during undergraduate and postgraduate education. 17 Additionally, lack of periodic continuing educational courses such as attending workshops and seminars is another contributing factor.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in line with most of previous similar studies in different countries, which reported very poor knowledge on MRONJ and BPs among dentists. 2,[13][14][15][16] This can be attributed to the insufficient exposure of dentists to these topics during undergraduate and postgraduate education. 17 Additionally, lack of periodic continuing educational courses such as attending workshops and seminars is another contributing factor.…”
Section: Discussionmentioning
confidence: 99%
“…Only half of the respondents gave a valid definition of a prophylactic examination of a patient receiving BP and when asked whether they are willing to perform prophylactic examinations of these patients, nearly half of the dentists would not or were not sure, which correlates with Vinitzky-Brener's research that found that 50% of the professionals did not feel comfortable treating patients on BP therapy. 23 The study in Ontario, Canada, also states that about 50% of dentists do not feel confident when treating a patient with BAONJ. 10 Bone 24 found that only 14.7% would deal with patients with BP complications.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the principles of the AAOMS regarding MRONJ were followed (1,4). Validated questionnaires from previous studies were prepared and given to participants (11,16,18). Detailed information about the study was given to participants, and their consent was obtained.…”
Section: Methodsmentioning
confidence: 99%
“…It is important for dentists, clinicians, and patients to be aware of the potential adverse effects of antiresorptive and anti-angiogenic drugs (11). A few studies have evaluated the levels of knowledge and awareness of dentists regarding BRONJ (11,(15)(16)(17). The purpose of this study was to evaluate the awareness and knowledge of dentists regarding MRONJ.…”
Section: Introductionmentioning
confidence: 99%